An H∞ filter based active damping control strategy for grid-connected inverters with LCL filter applied to wind power system. (January 2023) - Chen, Run; Zeng, Jun; Huang, Xiangmin; Liu, Junfeng
Highlights: A novel active damping strategy based on H∞ filter for inverters with LCL filter is proposed. The H∞ filter is used to estimate the capacitor current and feed it into the control loop to achieve resonance damping without additional current sensor. Stability can be guaranteed even if uncertainties exist in grid impedance and filter parameters. Both of simulation and experiment verify the feasibility and advantages of the control strategy. Abstract: Since the LCL filter has good performance to attenuate high frequency harmonics, it is widely used in wind power inverters. But it can cause high-frequency oscillations and instability, which limits its application in wind power system. For an LCL-type grid-connected inverter, the conventional capacitor-current-feedback type active damping control strategy can retain the high-frequency characteristics of LCL filter while suppressing the resonant peak effectively, with the drawback of requiring additional current sensors. Therefore, an H ∞ filter based active damping strategy of LCL grid-connected inverter is proposed. The state space model and the process noise model of the LCL inverter are built, and then the general model of the standard H ∞ control problem is derived, which helps to solve the H ∞ filter. The H ∞ filter can estimate the filter capacitor current according to sample values of the injected current and the voltage of the point of common coupling, and the estimation accuracy can be guaranteed even if parameter perturbations exist in the LCL filter. The proportional resonant controller is adopted to track the grid current. Therefore, the proposed control strategy can effectively suppress the resonance peak of the LCL filter without additional current sensors and be insensitivity to system parameter perturbations. The simulation and experimental results verify the feasibility and superiority of the proposed method.